Systematic Literatur Review : Cadabra sebagai Media Belajar untuk Mengetahui Kemampuan Peserta Didik - Winda Winata S. Pane; Yahfizham Yahfizham (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explore the use of Cadabra as a learning medium to asseses students’ abilities. Cadabra is software that facilitates the visualization and understanding of complex mathematical concepts, thereby enhancing students’ computational skills. Through a systematic literature review, this research analyzes the effectiveness of Cadabra in improving students’ understanding of mathematical concepts and analytical thingking skills. The findings indicate that integrating Cadabra into the learning motivation and outcomes,as well as provide real-time feedback that assists educators in indetifying individual students’ strengths and weaknesses.